A Sporting and Peronist Youth in the Making: The High School Students Union (UES) in Argentina (1952–1955) - Hémeury, Lucie (Frontiers in Sports and Active Living, 2020)
This article examines the history of the High School Secondary Students (Unión de Estudiantes Secundarios or UES), a sporting and cultural youth association created by the Peronist government in 1953. From its inception, this institution has been compared by sectors of the opposition to Fascist and Nazi youth organizations and accused of politically enlisting and morally corrupting Argentine youth. Based on institutional archives, UES publications and Perón’s speeches, this study offers a contribution to the historiographical debates on the history of youth, sports and Peronism. It shows how the creation of the UES relates to the social, educational and sports policies of the regime. The article analyses the objectives pursued by the government, but also the limits and contradictions of this attempt to mobilize young people through sports activities.